A note on the predictive content of PPI over CPI inflation: The case of Mexico - José Sidaoui; Carlos Capistrán; Daniel Chiquiar; Manuel Ramos-Francia (Banco de México, 2009)
This note studies the causal relationship that may exist between the producer price index (PPI) and the consumer price index (CPI). In contrast with previous international studies, the results suggest that, in the case of Mexico, information on the PPI seems to be useful to improve forecasts of CPI inflation. In particular, CPI inflation responds significantly to disequilibrium errors with respect to the long-run relationship between consumer and producer prices. These results are based on in-sample and out-of-sample tests of Granger causality, in the context of an error correction model.
Keywords: C32; C53; E31; E37; 330; Cointegration; Forecast evaluation; Granger causality; Vector error correction